Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.